Quantitative analysis of the fluvial geomorphology and erosion on Hainan island: implications for the source-to-sink system in the NW South China Sea - Qiu, Kai; Lei, Chao; Tang, Chao; Yang, Rong; Willett, Sean; Ren, Jianye (Frontiers in Marine Science, 2024)
The sediment delivery from Hainan island into the NW South China Sea during the Quaternary is less well-defined. An investigation into the uplift, exhumation and fluvial geomorphology of the Hainan island is crucial for improving our understanding on the source-to-sink system in this region. In this study, we employed the digital elevation analysis, the stream power incision model and the cosmogenic nuclide isotope analysis to unravel how and why the Hainan island provide sediment to the NW South China Sea. The results show that the average HI values of the main catchments on the Hainan island are below 0.35, which indicates that the rivers on the Hainan island tend to be stable. After mapping the channel steepness index of the Hainan island, a high channel steepness index is constrained in the central and western Hainan island. The χ analysis shows minor variations in χ values across the Hainan island, except of the watershed between the Wanquanhe and Nandujiang rivers, as well as that between the Changhuajiang and Nandujiang rivers, which indicates the potential migration of the river watersheds here. In addition, we carried out the cosmogenic nuclide 10Be analysis on the river sand from the Hainan island. The spatial distribution of 10Be concentrations is identified to be high in the west and low in the east. The catchment-averaged erosion rates are quantified to be 35 m/Myr, 42.5 m/Myr and 69.9 m/Myr for the Changhuajiang, Wanquanhe and Lingshuihe catchments, respectively. We also estimated the sediment deliveries from the Changhuajiang, Wanquanhe and Lingshuihe catchments to the Qiongdongnan and Yinggehai Basins to be 0.46 Mt/yr, 0.45 Mt/yr and 0.21 Mt/yr, respectively. We compared our results of the fluvial geomorphology analysis and erosion rate estimates of the Hainan island with those of the Taiwan island. We concluded that the difference of the erosion pattern and river evolution of the Hainan and Taiwan islands may be associated with the variation of the tectonics. Our investigation on the evolution of the Hainan island will improve our understanding on the source-to-sink systems in the NW South China Sea.